Pengaruh Profitabilitas dan Leverage Terhadap Manajemen Laba (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Food and Beverage Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2017-2021) - Anisya, Rahmi; Yentifa, Armel; Rosalina, Eka (Jurusan Akuntansi Politeknik Negeri Padang, 2023)
This study aims to determine the effect of profitability and leverage on earnings management (a case study in a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange for the 2017-2021 period). This research is a quantitative research. The sampling method was carried out using a purposive sampling technique. This study uses secondary data, namely from the financial reports of manufacturing companies in the food and beverage sub-sector which are listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample used in this study was 70 company data, with 2 outlier company data, so that the total sample used was 68 company data. The data analysis used was multiple linear regression analysis using the SPSS Version 25 program. Based on the results of the data processing it can be concluded that Profitability and Leverage have a positive and significant effect on Earnings Management (Case Study in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Stock Exchange Indonesia Period 2017-2021).